A comparative analysis on optical, photo luminescence and laser damage properties of conventional and uniaxial method grown semi organic nonlinear optical material – sodium potassium tartrate tetrahydrate. (16th April 2019) - Purusothaman, R.; Shankar, M.; Dennis Raj, A.; Vimalan, M.; Rajarajan, K.; Vetha Potheher, I.
Abstract: Bulk growth of (010) oriented Sodium Potassium Tartrate Tetrahydrate (SPTT), a Nonlinear Optical single crystal was grown by solution growth technique in uniaxial and conventional methods. Optically transparent single crystal of diameter 20 mm and length 150 mm was harvested by uniaxial method in a period of 25 days and dimensions upto10 mm ×5 mm ×3 mm by conventional method within 15 days. The grown crystal was confirmed by single crystal X-ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) analysis. Phase purity was checked with Powder XRD (PXRD) analysis. Uniaxial method grown crystal has higher transmittance than the conventional grown crystal. The Second Harmonic Generation (SHG) efficiency was found to be 0.9 times higher than KDP and laser damage threshold also measured and reported. Broad Photoluminescence (PL) emission was observed at 350–449 nm from the crystals grown by both the methods and it arises due to the ultraviolet and violet of visible spectral emissions. Positive photo conducting nature of the grown crystals was confirmed by photoconductivity measurements.